The Antioxidant Properties and Biological Quality of Radish Seedlings Biofortified with Iodine - Anna Krzepiłko; Agata Święciło; Iwona Zych-Wężyk (Agronomy, 2021)
Iodine is an essential trace element for humans, and iodine deficiency is a significant health problem. In this study, an improved method for iodine biofortification based on seed germination was established. Solutions of KI (0.15, 0.30, 0.75 and 1.5 mg∙g−1 of seeds) were applied to germinating radish seeds of two cultivars Raphanus sativus L. var. sativus: Warta and Zlata. Compared with the control (seeds treated with water) the iodine content (in the radish sprouts produced by germinating seeds treated with KI were approximately 112.9–2730 times higher. The application KI rates did not adversely affect the biological quality of the radish sprouts. Regarding the biological quality of the iodine-enriched seedlings, we determined their length, dry mater, protein, soluble sugars, chlorophylls, total phenol, ascorbic acid, thiol group content and total antioxidant capacity. The effect of potassium iodide on the selected parameters of their biological quality varied depending on the KI doses and radish cultivars. The results showed that the most appropriate biofortification application rates were 0.15 and 0.30 mg KI per g seeds, because the enriched seedlings had excellent biological quality parameters.